PENYULUHAN TENTANG BAHAYA KEBAKARAN AKIBAT LISTRIK BAGI WARGA RW 01/RT 02 KELURAHAN KARANGANYAR KOTA MAKASSAR - Patabang, Simon; Leda, Jeremias M. (Batara Wisnu : Indonesian Journal of Community Services, 2024)
A fire incident is something that is not expected to happen, therefore awareness and awareness of the occurrence of a fire disaster needs to be instilled in the minds of the community from an early age. The community must have knowledge about the impact of losses experienced if a fire disaster occurs. One of the causes of fires in the middle of residential areas is due to short circuits or short circuits in electrical cables. To prevent fires from occurring in residential areas, education is being conducted about preventing fires from occurring due to short circuits. Extension activities are carried out in residents' homes by providing knowledge about the introduction of various types of cables and how to connect electrical cables correctly and safely. Based on the results of the outreach carried out, it is known that the public increasingly understands the importance of preventing fire disasters that can occur due to short-circuited electrical cables. Residents have realized that fires can result in huge losses for all residents. With this education about fires, the level of awareness among residents regarding the use of electrical components and tools will increase